Determinants of MSME Success: The Mediating Role of Innovation in Entrepreneurial Characteristics and Social Capital - Muhammad Arief; Isep Amas Priatna; Rasyid Widada (Journal of Innovative and Creativity (Joecy), 2026)
Despite the dominant contribution of Micro, Small, and Medium Enterprises (MSMEs) to Indonesia's GDP, challenges regarding sustainability and competitiveness remain crucial issues. This study aims to analyze the mechanism of influence of entrepreneurial characteristics and social capital on MSME success through the mediating role of innovation. Employing an explanatory quantitative design, this study involved 53 MSME owners in Bogor Regency selected via purposive sampling with a criterion of at least 3 years of operation. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results demonstrate that innovation plays a vital role as a full mediator in the relationship between entrepreneurial characteristics and business success. Interestingly, the findings indicate that social capital has no significant effect on business success, either directly or through innovation. The study concludes that internal entrepreneurial characteristics are a superior determinant compared to external (social) capital in driving innovation and business success. Practical implications suggest that stakeholders should focus more on enhancing innovation capacity and entrepreneurial character rather than merely expanding networks.